PENGENALAN FIBER OPTIK MENGGUNAKAN AUGMENTED REALITY SEBAGAI PENGENALAN ALAT PADA SISWA SMKN 1 PURWAKARTA - Legira Putri Alina Sidik; Dian Permata Sari; Leonardi Paris Hasugian (LPPM Universitas Abdurrab, 2026)
Learning about fiber optic materials in vocational high schools still faces several challenges, particularly due to limited practical equipment and the absence of interactive digital learning media that students can access independently. This has implications for students' less-than-optimal understanding of the shapes and functions of fiber optic equipment. This research aims to design and evaluate Augmented Reality-based learning media as an interactive tool to introduce fiber optic practical equipment to students. The method applied is the 4D development model, encompassing the Define, Design, and Modified Develop stages. The Modified Develop stage is an adaptation of the Develop stage, with a primary emphasis on the evaluation and improvement of the learning media design. This approach is carried out through two rounds of usability testing, without proceeding to the Disseminate stage. In the testing, 15 students from the Computer Network and Telecommunications Engineering (TJKT) department participated as research subjects. The evaluation shows significant progress in the media design quality after revisions, reflected in the increase of the UMUX score from 6.7 in the initial testing to 7.0 in the subsequent testing. Additionally, there were improvements in various aspects, including effectiveness, efficiency, learnability, error aspects, and satisfaction. Students successfully completed all tasks with better performance and expressed high satisfaction with the design. Therefore, it can be concluded that the designed Augmented Reality-based learning media has potential as a support for fiber optic learning in vocational high schools and is worthy of further development toward the implementation stage.